(untitled) (Journal of Hama University, 2021)
This research was conducted to determine the effect of the quality of e-banking services in its five dimensions (tangible, reliability, responsiveness, safety, and empathy) on customer satisfaction in in a sample from the private banks operating in Syria. The researcher distributed (175) questionnaires to a random sample of bank customers under study. (175) questionnaires were retrieved and (13) questionnaires were excluded, Thus, the number of questionnaires that have been discharged is (162). The researcher analyzed the data using the Statistical Analysis Program (SPSS 25). At the end of this research, the researcher reached a number of conclusions, the most mportant of which are: There is a significant effect of the quality of e-banking services in its five dimensions (tangible, reliability, responsiveness, safety, and empathy) on customer satisfaction in the banks under study.